City dwellers' perception of environmental hazards and risks in Dhaka city (Journal of the Asiatic Society of Bangladesh, Science, 2021)
This paper examines the social perceptions against the existing overall environmental hazards and pollutions of different residential areas of Dhaka Metropolitan area. The empirical data have been collected through a semi-structured questionnaire from 180 households. The findings reveal that more than 60% of people in residential areas are at high risk for environmental hazards due to the vast population density and unplanned high-rise buildings. Furthermore, on average, more than 53% of respondents have uttered various pollutions emphatically air, dust and noise pollution which are now common environmental phenomena of residential areas for unruly behaviors of dwellers and mismanagement of respective authorities. Moreover, the lack of open space is a burning question for the city dwellers, which causes a ventilation crisis through accelerating indoor pollution claimed by 95% of slum dwellers. After all, slum dwellers are more deprived of overall urban facilities, and abiding in unhygienic conditions made them more prone to fire hazards and severe health disorders. So, the study suggests that policymakers and city corporation authorities should be more concerned and taken proper initiatives to eradicate multifaceted issues to fabricate a sustainable environment for city dwellers.J. Asiat. Soc. Bangladesh, Sci. 47(1): 47-65, June 2021